Flexibilização organizacional e contexto de incerteza: um estudo com gestores de organizações temporárias - Borges, Maurel Granatto (2011)
This research explores the relation between the environmental context and the organizational structures immersed in it. It assumes that the context of less environmental uncertainty tend to favor rigid, formal structures, awarded with predictability, however, when the uncertainty is higher, more flexible structures emerge, better adapted to the uncertain. Having as a source, temporary organizations dedicated to the pursuit of projects and, as analysis unit, their managers, it´s about descriptive study using quantitative and qualitative procedures. In a first questionnaire phase applied in the form of survey, a sample was collected from 181 answers - 26.23% of feedback on the universe. The responses received quantitative treatment seeking behavior patterns. To deepen the results of this stage, three groups were discriminated according to patterns of responses, and, from these groups, responding representatives were selected for semi-structured interviews. The search result confirms the postulate of the theoretical reference: in light of the perception of the context of uncertainty, the manager seeks the flexibility of the organizational structure to allow him to cope. The results also suggest that the managers show a strong reliance on quantitative and qualitative tools and tend to use them to predict and thus control scenarios. However, it is recorded that a small group suggests to distrust of tools to predict scenarios, prefers to allocate resources to uncertain events in preparation, in the impact to the objectives of a project. Another interesting result of the research is what reveals the strong perception of the managers in face of faced the uncertainty of the munificence, which corresponds to the potential of the impact on the sustainability of the business since it finds itself related to the availability of the resources. Recommended by the referential literature, limited rationality presents itself in qualitative analysis from the interviews, which shows that managers act restricted by factors such as time and available information, as well as their own capacity of analysis. In conclusion, it can be said then that the work helps to establish the literature, to clarify beliefs and courses of action in the face of uncertainty. Above all, it shows that in view of the uncertainty associated with projects to be accomplished in the future, flexibility takes precedence over the structural rigidity.